Gait kinetics before and after total hip arthroplasty in people with unilateral hip osteoarthritis - Lingling Zhong; Patrick Wai-Hang Kwong; Jack Jiaqi Zhang; Ananda Sidarta; Clare Chung-Wah Yu (PLoS ONE, 2025)
Background Total hip arthroplasty (THA) is a common intervention for end-stage osteoarthritis (OA) that improves gait kinetics. However, full restoration of mobility through THA remains elusive. Limited studies have examined changes in hip kinetics throughout the entire stance phase. In this study, we explored the differences in hip moment and power between preoperative and postoperative states in unilateral hip OA and compared these patients with healthy controls. Methods A secondary analysis was conducted using a publicly available dataset. A total of 69 healthy controls and 67 participants with a history of THA for whom preoperative and postoperative data were available for analysis were included in the study. Motion capture data obtained using the Plug-in Gait marker set was analyzed and modeled in Visual3D. Statistical parametric mapping (SPM) paired t tests were used to determine the differences in hip moment and power during the stance phase between preoperative and postoperative states. Independent-samples t tests were conducted to compare these metrics in healthy controls and both preoperative and postoperative groups. SPM regression was used to analyse the correlation between changes in walking speed and hip kinetics. Results Significant changes in hip sagittal moment (0.0–4.3% stance phase, P = 0.037; 66.7–100.0% stance phase, P < 0.001), frontal moment (9.9–38.7% stance phase, P < 0.001; 55.2–93.7% stance phase, P < 0.001) and hip power (50.8–70.8% stance phase, P < 0.001; 84.2–100.0% stance phase, P < 0.001) were observed between the preoperative and postoperative participants, and a minor difference was noted in the total difference duration between the postoperative participants and healthy controls. The postoperative participants experienced hip kinetic deficits, and a significant association was observed between hip kinetics and changes in walking speed. Conclusion The hip kinetics of patients gradually normalise by 6 months after THA. Specific exercise programmes may be required to improve the specific gait patterns deficits of patients undergoing THA.